Rangeland evaluation and perceptions of the pastoralists in the Borana zone of southern Ethiopia - Bayene, Solomon Tefera (University of the Free State, 2003)
The study was conducted in the Borana rangeland of southern Ethiopia. In the last few decades the Borana rangelands have been degraded while the pastoralists adhered to the traditional grazing strategies. The main aims with this study were to investigate the soil characteristics as well as aboveground plant communities and to assess the condition of the rangeland. In addition, the pastoralists' perceptions and cattle-rangeland management practices were evaluated. The botanical composition of the grass layer, woody vegetation structure, soil and the rangeland condition were studied in four communal grazing areas (Did Yabello, Did Harra, Dubuluk and Melbana), three land use systems (communal land, government ranch and traditional grazing reserve) and along distance gradients from water source. Species composition and basal cover of the grass layer was estimated using frequency of occurrence of plant species. Woody plant data were standardized to tree equivalent ha-l (l TE = 1 tree, 1.5 m high). Rangeland condition was assessed based on ecological condition index, weighted palatability composition of the grass layer, the structure of woody plants and soil compaction. Soil seed bank was studied under three land use systems and along a distance gradient from water source. Survey on cattle-rangeland management practice and pastoral perceptions was conducted on 40 individual households and 118 elders (7 per group). Survey results of the pastoral households and elders indicated that the average household in the study area was 7 members. The percentages of male and female children who attended schools were 26 % and 9 % respectively. Livestock holding per household was estimated to be 14 cattle, 10 goats, 6 sheep and 2 camels. Cultivation is widespread in the study area. Major constraints in livestock production were in order of importance: drought, feed shortage, water scarcity, animal diseases, predators and communal land tenure. According to the pastoralists, contributing factors to rangeland degradation were in descending order: recurrent drought, human and livestock pressure, expansion of cultivation, ban on fire and development of water ponds. A total of 49 grass species were identified in this study. The communal land had higher and lower percentages (P<0.05) of annual and perennial grasses, respectively, than the government ranch and the traditional grazing reserve. There were no marked differences (P>0.05) among the four communal grazing sites and the three different distances from water concerning both annuals and perennials. The occurrence of Chrysopogon aucheri was higher (P<0.05) on the government ranch (23 %) and traditional grazing reserve (27 %) than on the communal land (14 %). The frequency of C. aucheri did not vary between the communal grazing sites (average = 14 %) and along distance gradient from water (average = 12 %). Leptothrium senegalensis and Chloris myriostachya did not vary (P<0.05) between the land use systems (average = 4 % and 1 %, respectively) and along the distance gradient from water (average = 2 % for both species). The frequency of Sporobulus nervosus was highest (P<0.05) in the communal land (13 %), whereas the occurrence of S. pyramidalis did not differ markedly (average = 32 %) between the land use systems (P>0.05). Both species did not show prominent variations along the distance gradient from water (average = S. nervosus-14 % and S. pyramidalis-36 %). Grass basal cover was fairly low and similar in the land use systems, communal grazing sites and distance gradients from water. A total of 54 woody plants were identified. Total density of woody plants was higher (P<0.001) on the communal land (l 083 TE ha-I) or the government ranch (l 188 TE hal) than on the traditional grazing reserve site. Within the communal grazing sites, the densities at Did Yabello (l 318 TE ha"), Did Harra (l 088 TE ha") and Melbana (1 178 TE ha") were higher (P<0.05) than on the fourth site, Dubuluk. Results from the distance gradient from water revealed that differences were not significant (P>0.05) between the near, middle and far sites (average = 1 150 TE ha-I). Overall figure showed the advancement of woody encroachment in the semi-arid Borana rangelands. The most important invaders were Commiphora africana, Grewia tembensis, Acacia drepanolobium and A. brevispica. Soil chemical analysis revealed low nutrient contents, which did not vary significantly (P>0.05) in all the study areas. Similarly, differences in pH, soil texture, soil bulk density and soil compaction were not significant. Assessment of rangeland condition indicated that both ecological condition index (ECI) and weighted palatability composition (WPC) were highest on the government ranch (711 and 55 %, respectively). Along the distance gradient from water, differences in rangeland condition (P>0.05) were not significant (average: ECI = 533 and WPC = 29 %). Within the communal grazing sites, Dubuluk and Melbana had relatively higher ECI and WPC values (average: 602 and 36 %, respectively) than the other two sites (average = 520 and 25 %, respectively). The soil seed bank study revealed that a total of 44 plant species were identified. Of these, 25 % were grasses and 75 % were non-grass plant species. As for the land use systems, seedling and floristic density of the graminoids were higher (P<0.05) on the traditional grazing reserve (798 seedling m-2 and 361 plants m-2, respectively) than on the communal land and the government ranch. Along the distance gradient from water, the differences were not significant (P>0.05). Similarity between grass flora of seed bank and above ground plant community was low. It can be concluded in this study that the deteriorating conditions of the Borana rangelands were revealed by changes in the structure and composition of the grass layer, woody vegetation, soil fertility and by the status of the soil seed bank. Bush encroachment is the critical problem. Therefore, workable control programs need to be devised immediately. It is also vital to develop a clear policy at national level on the use and management of the communal rangeland resource.
Thesis (Ph.D. (Animal, Wildlife and Grassland Sciences))--University of the Free State, 2003
Keywords: Range management -- Ethiopia -- Borana Plateau; Pastoral systems -- Ethiopia -- Borana Plateau; Rangelands -- Ethiopia -- Borana Plateau